2013
DOI: 10.1111/1462-2920.12167
|View full text |Cite
|
Sign up to set email alerts
|

Honey bee larval peritrophic matrix degradation during infection with Paenibacillus larvae, the aetiological agent of American foulbrood of honey bees, is a key step in pathogenesis

Abstract: Paenibacillus larvae, the aetiological agent of American foulbrood (AFB) of honey bees, causes a fatal intestinal infection in larvae and invades the haemocoel by breaching the midgut. The peritrophic matrix lining the midgut epithelium in insects constitutes an effective barrier against abrasive food particles, xenobiotics, toxins and pathogens. Pathogens like P. larvae entering the host through the gut first need to overcome this barrier. To better understand AFB pathogenesis, we analysed the fate of the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 46 publications
(92 reference statements)
0
50
1
1
Order By: Relevance
“…This phenomenon has been attributed to the growing PM already in the early days of AFB research [17], [18]. Recently, we demonstrated that the honey bee larval gut is lined by a chitin-containing PM which is degraded during P. larvae infection [19], confirming earlier results showing that the PM is the first barrier the bacteria have to overcome when trying to breach the epithelium and to enter the haemocoel [20]. Proteases and chitin-degrading proteins are most likely involved in this process.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…This phenomenon has been attributed to the growing PM already in the early days of AFB research [17], [18]. Recently, we demonstrated that the honey bee larval gut is lined by a chitin-containing PM which is degraded during P. larvae infection [19], confirming earlier results showing that the PM is the first barrier the bacteria have to overcome when trying to breach the epithelium and to enter the haemocoel [20]. Proteases and chitin-degrading proteins are most likely involved in this process.…”
Section: Introductionmentioning
confidence: 84%
“…Recently, the genomes of representatives of two P. larvae genotypes, ERIC I and ERIC II, were sequenced, annotated and used for comparative genome analysis [26]. Surprisingly, no complete, uninterrupted and, hence, putatively functional gene coding for a classical chitinase could be detected in any of the genomes [26] posing the intriguing question: how is the described chitin-degradation by P. larvae during infection [19] achieved? We are now answering this question by describing the identification and functional characterization of P. larvae Pl CBP49, a novel member of the AA10 (formerly CBM33) family of chitin-binding and –degrading LPMOs.…”
Section: Introductionmentioning
confidence: 99%
“…The PM of honey bee larvae consists mainly of chitin and its functional integrity is essential for larval survival [37]. Degradation of the PM during P. larvae infection and the ability of P. larvae to metabolize colloidal chitin could both be demonstrated [37].…”
Section: Identification and Role Of Secondary Metabolitesmentioning
confidence: 99%
“…The PM of honey bee larvae consists mainly of chitin and its functional integrity is essential for larval survival [37]. Degradation of the PM during P. larvae infection and the ability of P. larvae to metabolize colloidal chitin could both be demonstrated [37]. PlCBP49, a chitinbinding and -degrading enzyme expressed by both P. larvae genotypes, was shown to be crucial for PM degradation during larval infection and to mediate chitindegradation via a metal-ion dependent, oxidative mechanism [38 ].…”
Section: Identification and Role Of Secondary Metabolitesmentioning
confidence: 99%
“…The PM also protects the midgut epithelium from mechanical and biochemical damage by abrasive food particles, digestive enzymes and pathogens [7]. In the development of American foulbrood, degradation of the PM occurs in the gut of P. larvae -infected larvae, which enables P. larvae to access the underlying epithelial cells directly and attack them [5]. At the advanced stage of EFB, the PM also tended to have degenerated or be absent in some parts.…”
Section: Discussionmentioning
confidence: 99%